HEALTH NEEDS OF THE PEOPLE OF PREK TORL – CAMBODIA: A CROSS SECTIONAL STUDY - Mitra Andini Sigilipoe; Katrin Tsang (Faculty of Medicine Universitas Kristen Duta Wacana, 2015)
Background: Several studies have mentioned about health problems of people who lives within a landfll area, especially for pregnant mothers and the health outcomes such as low birth weight, spontaneous abortion, infant mortality, and other health issues. In Prek Torl-Pnomh Penh-Cambodia, about 200 households, who are living under poverty line, dwell in a slum surrounded by heaps of decaying wastes. These households consist of women within productive age of 18-49 years old, and they are exposed to the hazard of wastes every single day. Objectives: The study is aimed to assess the need of Prek Toul's population, especially health problems regarding maternal and child health. Methods: Household surveys were carried out in June 2012 and 2013. In 3 days, a team from S.H. Ho College, under supervision of Prof. Katrina Tsang, conducted the survey to 88 and 90 households, respectfully. Data was analyzed using frequency and compared with Cambodia's 2010 Demographic and Household survey result. Statistical tests were also used to see if there was any correlation or association between household income, education level or status, antenatal service, and infant mortality. Conclusion: The fndings of this study suggested that low level of education and income is connected with the uptake of antenatal service. The perception of access to health care is not in line with the uptake of antenatal service. More qualitative studies might be needed to explore the reason for that issue. Further studies may shed more light on the reason of why women did not use antenatal service, and in time may help in designing new interventions for delivering more suitable maternal and child health care for the particular population